Investigating level of ownership and utilization of insecticide treated nets in Igbo Eze South local Government area of Enugu State - Christian Eze; Chijioke Okoli; Enyi Etiaba; Obinna Onwujekwe (International Journal of Medicine and Health Development, 2016)
Background:Malaria remains one of the leading causes of morbidity and mortality worldwide especially in Africa and Nigeria in particular. Aim: The study investigated level of ownership and utilization of ITNs, with focus on the availability of ITNs, level of awareness about ITNs, ownership, utilization of ITNs and factors influencing ownership and utilization of ITNs in Igbo Eze South Local Government Area of Enugu state. Subject and Methods: Cross sectional descriptive survey was adopted. Data were elicited from pregnant women and nursing mothers in three public health facilities located in urban, semi-urban and rural area within the local government. The quantitative data were analyzed to determine frequencies and percentage of ownership, utilization, factors influencing ownership and utilization. Also Chi-square was generated to determine association of age and education with ownership and utilization of ITNs. Results: The study revealed that ownership and utilization were both high (81%). However, factors influencing ownership and utilization of ITNs were discontinuity of distribution of free nets (78.4%), fear of chemical impregnated with ITNs (72.5%) and poor attitude towards the use of ITNs (97.3%) have the most influence. In addition, poor knowledge (66.0%) and cultural beliefs (63.3%) affected ownership and utilization of ITNs. The study revealed that the utilization of ITNs differed by level of age and education. Conclusion: Concerted efforts need to be made to resolve the various factors that constrain the ownership and use of ITNs. Also, efforts should be sustained to scale up the distribution and ownership of ITNs in the study area.